Supportive and Palliative Care Needs of the Older Adults with Stroke and Neurological Diseases: An Estimation using data from Longitudinal Ageing Study in India. - Immanuel, Terrymize; Salins, Naveen; Sundararaj, Jenifer Jeba; Gursahani, Roop; Thomas M, Benson (Indian Journal of Palliative Care)
Objectives: The prevalence and burden of neurological diseases are high among the older age group. Stroke and other neurological diseases significantly impair functional capacity and lead to poor quality of life. This study aims to provide a national-level estimate for palliative and supportive care needs among older Indian adults with stroke and other neurological diseases. Materials and Methods: The Longitudinal Ageing Study in India (LASI), a national-level survey of older adults, was used as a representative sample to estimate palliative and supportive care needs. The supportive and palliative care indicator tool income setting (SPICT-LIS) was used to identify palliative care needs in older adults with stroke and other neurological diseases. A total of 31,902 older adults aged 60 years and above were identified from the LASI data, and among them, 1458 older adults with stroke and other neurological diseases were selected for the analysis. The SPICT-LIS indicators were compared with the selected LASI data. Both univariate analysis and multivariate logistic regression were performed to determine the association between supportive and palliative care needs and background characteristics of older adults. Results: The analysis showed that 63.6% of older adults with stroke and other neurological diseases in India have supportive and palliative care needs. In regression analysis, the burden of supportive and palliative care needs was observed to be high among older adults who were in the underweight, overweight/obese category, who experienced ill-treatment, and who had diabetes and hypertension. In contrast, the burden of supportive and palliative care needs was observed to be low among older adults with stroke and neurological diseases who belonged to richer and richest economic quintiles, those receiving at least one social support scheme, those engaged in social activity and those performing physical activity. Conclusion: The palliative care needs among the older adult population with stroke and other neurological diseases in India are high. The findings of this study underscore the importance of screening for supportive and palliative care needs among patients with stroke and other neurological diseases to identify these unmet needs. The workforce trained in the provision of generalist and specialist palliative care will be required to meet this need, and the population of older adults is estimated to double in the next three decades.